Alterity Politics : Ethics and Performative Subjectivity - Nealon, Jeffrey T. (Jeffrey Thomas) (Book collections on Project MUSE., 1998)
In conventional identity politics subjective differences are understood negativively, as gaps to be overcome, as lacks of sameness, as evidence of failed or incomplete unity. In Alterity Politics, Jeffrey T. Nealon argues instead for a concrete and ethical understanding of community, one that requires response, action, and performance instead of passive resentment and unproductive mourning for a whole that cannot be attained.